Comparing Justice-Involved and Community Adolescents’ Emotional Well-Being and Feelings of Social Connection During COVID-19: A Daily Diary Study of Adolescents’ Social Contact - Thomas, April Gile (Criminal justice and behavior, 2025)
This study utilizes 6 weeks of electronic daily diary self-assessments across more than 1 year of the COVID-19 pandemic to examine associations between adolescents’ phone and video social contact with friends, family, and others over time. The sample includes justice-involved juveniles adjudicated to probation or incarceration and a comparison community sample of never-arrested adolescents. Findings reveal that community youth did not demonstrate positive emotional gains from social contact via phone or video during the pandemic and at times experienced more negative emotion on days with virtual social contact; however, such contact was especially beneficial for justice-involved youth, who had better self-conceptions and stronger feelings of social connection (although more loneliness as well) on days when they engaged in phone or video contact with friends or family. Thus, social contact via phone or video may serve to close the gap in emotional well-being between justice-involved and community adolescents.